Decomposition of mulching and release of nitrogen and phosphorus in a sand oat-soybean rotation under no-tillage - Wisniewski, Celina; Holtz, Guilherme Pimentel (Pesquisa Agropecuaria Brasileira, 1997)
This paper aimed to study the dynamics of corn (Zea mays) and sand oat (Avena strigosa L.) mulchings and of N and P release during a sand oat/soybean (Glycine max Merril) rotation under no-tillage. Weight loss and C, N and P content of corn and sand oat mulchings were periodically monitored during 370 days in a sand oat/soybean rotation under no-tillage, on an Oxisol, typic Haplustox soil at the Batavo Demonstration and Experiment Field in Carambeí, PR, Brazil. The corn mulching decomposed more slowly, loosing 49% of weight in 149 days, due to its higher C/N ratio (43:1), to a more heterogenous distribution and to the greater quantity of initial residue (9.8 vs. 6.8 t.ha-1). The sand oat mulching lost 71% of weight in 179 days. The average contents of C and of N in the corn mulching were 428 and 10 g.kg-1, respectively, and 415 and 17 g.kg-1 in sand oat mulching. The contents of P decreased in the period from 1.2 to 0.9 g.kg-1 in the corn and from 1.6 to 1.0 g.kg-1 in the sand oat. A mineralization of 48% of the C, 51% of the N and 77% of the P was estimated. In the sand oat mulching, 71% of the C, 75% of the N and 85% of the P were mineralized. The average carbon/phosphorus ratio of corn mulching was superior (470:1) to that of the sand oat (319:1).